Nurse preceptors' perceptions of benefits, rewards, support and commitment to the perceptor role in the intensive care units of five major academic hospitals in Gauteng - Viljoen, Alida (My University, 2015)
The preceptorship model is widely used in both undergraduate and postgraduate nursing education. Primarily, preceptors engage in preceptorship to share knowledge, obtain recognition and achieve job satisfaction. However, the same preceptors are facilitating integration of newly hired staff in Intensive Care settings and these experiences are relatively unknown. Preceptors are highly qualified and valued staff, who undertake this role in addition to their nursing responsibilities and the risk of burnout exists if asked to assume additional obligations without appropriate rewards and support. Consequently, needs and expectations necessitate understanding so that preceptors, preceptees and clinical facilities may benefit from such programmes. Purpose. The purpose of the study was to examine the relationships amongst preceptors’ perceptions of benefits, rewards, supports and commitment to the preceptor role. Method. A non-experimental, descriptive, correlational and quantitative survey design and a non-probability purposive sampling method were applied and used in this study. The setting for the research is the Intensive Care Units (n=13) of four major academic hospitals, including public and private sector, in Gauteng Province. The sample comprised of 80 (n=80) Intensive Care registered nurses, employed throughout the Intensive Care Units (n=13). Data was collected by means of a self-administered questionnaire (Dibert & Goldenberg, 1995) and participants were asked to rate all the items independently on a 4-point Likert scale. Findings. Data analysis determined the incidence of preceptor’s perceptions of the benefits, rewards, support and commitment to the preceptor role. Preceptors perceive there are benefits for the preceptor in preceptorship. The commitment of preceptors, if rewarded and part of a beneficial goal, was seen with a positive response. The study indicated that if preceptors perceive there to be support for their role, their commitment to the role of preceptorship increases. Years of experience, age and gender had no significant role in the preceptor commitment. Conclusion. Preceptors are committed to their role. It is the responsibility of the nursing education, health care institutions and nursing practice to provide benefit, rewards and support to sustain this role. Research in qualitative and quantitative studies on preceptorship is needed on this topic.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Nursing Johannesburg, 2014